Cadmium distribution in mature durum wheat grains using dissection, laser ablation-ICP-MS and synchrotron techniques. (May 2020) - Yan, Bofang; Isaure, Marie-Pierre; Mounicou, Sandra; Castillo-Michel, Hiram; De Nolf, Wout; Nguyen, Christophe; Cornu, Jean-Yves
Abstract: Understanding how essential and toxic elements are distributed in cereal grains is a key to improving the nutritional quality of cereal-based products. The main objective of this work was to characterize the distribution of Cd and of nutrients (notably Cu, Fe, Mn, P, S and Zn) in the durum wheat grain. Laser ablation inductively coupled mass spectrometry and synchrotron micro X-ray fluorescence were used for micro-scale mapping of Cd and nutrients. A dissection approach was used to quantitatively assess the distribution of Cd and nutrients among grain tissues. Micro X-ray absorption near-edge spectroscopy was used to identify the Cd chemical environment in the crease. Cadmium distribution was characterized by strong accumulation in the crease and by non-negligible dissemination in the endosperm. Inside the crease, Cd accumulated most in the pigment strand where it was mainly associated with sulfur ligands. High-resolution maps highlighted very specific accumulation areas of some nutrients in the germ, for instance Mo in the root cortex primordia and Cu in the scutellum. Cadmium loading into the grain appears to be highly restricted. In the grain, Cd co-localized with several nutrients, notably Mn and Zn, which challenges the idea of selectively removing Cd-enriched fractions by dedicated milling process. Graphical abstract: Image 1 Highlights: High-resolution maps of Cd distribution in durum wheat grain were produced. Cadmium accumulated most in the crease, and inside the crease, in the pigment strand. Cadmium was mainly associated to sulfur ligands in the vascular bundle area. Cadmium was relatively more concentrated in the endosperm than most nutrients. Cadmium accumulated in the same parts of the grain as Mn and Zn.